Development of an economic trait prioritization for Tilapia in Nigeria: Survey (deliverable 2) progress summary - Cole, Steven; Adams, Chris; Byrne, Tim (Abacusbio, 2024)
Deliverable 2 (participatory survey and typology analysis) uses economic weights calculated in Deliverable 1 (economic modelling) to capture trait preference and typologies based on survey feedback from key stakeholders. In Tilapia, these surveyed stakeholders will include farmers and hatchery operators, but may also encompass other value chain actors, including wholesalers /retailers depending on primary breeding objectives. The Deliverable 2 output will be a set of trait preference coefficients that fine-tune (up or down) economic values from Deliverable 1 based on input from each typology. Applying these trait preference coefficients to economic values help in understanding stakeholder’s trait improvement preferences and ensures the systematic integration of stakeholders’ preferences into selection and breeding decisions to support faster and more balanced rates of genetic gains and deliver improved fish species that meet industry needs.